Studies on functional education and literacy a handbook and user's guide (UP-ERP Research Team, 1996)
This book is an attempt to bridge the gap between research and practice and to ensure that researchers, policy-makers and practitioners in literacy and functional education can find a common ground for continued communication and cooperation towards the shared objective of helping our people to achieve the kind of education that is functional to their lives, and relevant to their needs and aspirations.